1999
DOI: 10.1046/j.1365-2222.1999.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

Nasal response to a single antigen challenge in patients with allergic rhinitis — inflammatory cell recruitment persists up to 48 hours

Abstract: Nasal challenge with the relevant antigen can induce a late response characterized by local accumulation of eosinophils, neutrophils and mononuclear cells persisting for 48 h and accompanied by release of ECP, MPO, LTB4 and histamine. These results indicate that a single antigen challenge in patients with allergic rhinitis causes prolonged inflammatory alterations which may contribute to the development of airway hyperreactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 34 publications
(59 reference statements)
3
48
0
1
Order By: Relevance
“…By applying our cut-oV most subjects with a positive sNPT presented a signiWcant nasal eosinophil increase compared with the subjects with a negative one, thus conWrming an exposure-induced eosinophilic inXammation, which was still evident 24 h after sNPT as previously reported in nasal lavage of AR and OR subjects (Miadonna et al 1999;Górski et al 2000). The detection of tryptase in supernatants of nasal blown secretions also demonstrated that this method is suitable to evaluate soluble luminal mediators.…”
Section: Discussionsupporting
confidence: 77%
“…By applying our cut-oV most subjects with a positive sNPT presented a signiWcant nasal eosinophil increase compared with the subjects with a negative one, thus conWrming an exposure-induced eosinophilic inXammation, which was still evident 24 h after sNPT as previously reported in nasal lavage of AR and OR subjects (Miadonna et al 1999;Górski et al 2000). The detection of tryptase in supernatants of nasal blown secretions also demonstrated that this method is suitable to evaluate soluble luminal mediators.…”
Section: Discussionsupporting
confidence: 77%
“…Indirect evidence is derived from the findings that the ligand PGD 2 is present in the nasal lavage fluid of patients with allergic rhinitis in response to allergen challenge (Naclerio et al, 1983;Miadonna et al, 1999) and DP2 expression is increased in allergic human nasal mucosa relative to nonallergic mucosa (Shirasaki et al, 2009). In Japan, ramatroban (Bayans), a dual DP2/TP antagonist, is clinically used for the treatment of allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%
“…CysLTs were also detected in nasal washings following antigen challenge in subjects with allergic rhinitis (Shaw et al, 1985;Miadonna et al, 1999) and have an ability to Correspondence to: Yoshihiko Chiba, Ph.D., Department of Pharmacology, School of Pharmacy, Hoshi University, 2-4-41 Ebara, Shinagawa-ku, Tokyo 142-8501, Japan Phone: +81-3-5498-5786 Fax: +81-3-5498-5787 e-mail: chiba@hoshi.ac.jp induce nasal obstruction in a guinea pig model of allergic rhinitis . The nasal obstruction induced by LTD4 was inhibited by pranlukast, a CysLT1-receptor antagonist, and N ω -nitro-L-arginine methyl ester (L-NAME), an inhibitor of NO synthase , suggesting an important role of NO released by an activation of CysLT1-receptors.…”
Section: Introductionmentioning
confidence: 99%